Memahami Peranan Perempuan Suku Minang Perantauan dalam Menjaga dan Meneruskan Komunikasi Budaya Matrilineal - Yanti, Wira (Jurnal The Messenger, 2014)
Wira Yanti, G.311.10.0045. Understanding Minang Settler Women s Role in Preserving and Continuing the Communication of Matrilineal Culture (A study case to Minang women in Semarang). Final Project: Study Program S1 Communication Study Semarang University.  The research is aimed at knowing the challenges and the roles of settler women (Minang ethnic) who stay in Semarang, as a minority group to preserve and continue the communication of matrilineal culture. The bases of the study are cultural communication, intra-cultural communication, symbolic interactionism and personal communication. One that is being questioned in the research is how to understand Minang women to preserve the communication of matrinilineal. The study used qualitative descriptive method by using the data from observation and reducing the data from indepth interview to be presented in a form of a research. Minang ethnic is a minority in Semarang however being settlers do not change the customs. Minang women in Semarang as main performers of matrilineal culture stay strong although they do not live in their hometown, they keep preserving and continuing the long-established matrilineal culture. All of their action is done to protect the traditional values.